Ibrutinib as monotherapy versus combination therapy in Chinese patients with relapsed/refractory mantle cell lymphoma: A multicenter study. (19th April 2022) - Zhang, Yuchen; Liu, Panpan; Cai, Jun; Jing, Hongmei; Zou, Liqun; Huang, Huiqiang; Wu, Yuanbin; Li, Wenyu; Zhong, Liye; Jin, Xueli; Ye, Xu; Feng, Ru; et al.
Abstract: Background: Ibrutinib has revolutionized the treatment of mantle cell lymphoma (MCL). Both ibrutinib monotherapy and ibrutinib‐based combination therapy are important salvage options for patients with relapsed/refractory (R/R) MCL. The real‐world efficacy and safety profile of the two strategies in Chinese patients with R/R MCL remain unclarified. Methods: In the present study, data of 121 R/R MCL patients who received either ibrutinib monotherapy ( N = 68) or ibrutinib combination therapy ( N = 53) in 13 medical centers in China were retrospectively reviewed. Results: With a median follow‐up of 20.5 months, the overall response rate was 60.3% versus 84.9% ( p = 0.003), complete remission rate was 16.2% versus 43.4% ( p < 0.001), and median progression‐free survival (PFS) was 18.5 months (95% confidence interval [CI], 12.1–21.8) vs. 30.8 months (95% CI, 23.5‐NR) (hazard ratio, 0.53 [95% CI, 0.30–0.93]; p = 0.025), with ibrutinib monotherapy and ibrutinib‐based combination therapy, respectively. Subgroup analysis showed that patients with male gender, no refractory disease, Ki67 <30%, previous line of therapy = 1, non‐blastoid subtype, and the number of extranodal sites involved <2 might benefits more from the combination therapy. Treatment‐emergent adverse events were similar, except for a higher incidence of all grade neutropenia in the ibrutinib combination group (12.7% vs. 32.0%, p = 0.017). Conclusions: Ibrutinib combination therapy demonstrated potentially superior efficacy and comparable tolerability to ibrutinib monotherapy. Ibrutinib‐based combination therapy could be one of the prominent treatment options for R/R MCL patients. Abstract : Compared to ibrutinib monotherapy, ibrutinib‐based combination therapy showed potentially superior efficacy for relapsed/refractory mantle cell lymphoma patients, with similar safety profile. Combination therapy based on ibrutinib could be considered as one of the prominent treatment options for this group of patients.